(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study is to develop a system to improve class content by allowing multiple teachers to share video data of PE classes and discussing this online. Initiatives to improve class content in Japan where the main focus is the teacher are known as Kounaikenshukai (In-school training program), and is highly regarded overseas under the name “Kounaiken”. However, it involves a lot of work, including prior preparation and holding discussion sessions etc. To address this problem, we developed a system that can be used online, anytime and anywhere without significant burden on those involved and which allows teachers to improve their educational practices and have fun at the same time. Online system allows the teachers to view video data from their classes and post their observations on an online computer screen (identify areas that can be improved). In response to this post, several other teachers make comments identifying areas where the teacher could have done things differently (discussion of areas that could be improved). Following this discussion, the participants can then discuss and finalize improvement strategies. Each of the three teachers accurately identified areas of their own classes that could be improved. Teachers were able to identify scenes from the video which typified the areas which could be improved and discussions concerning these proved to be productive. The three teachers provided identical improvement strategies over the course of the discussions which provided specific steps to improve class content.